Gender-Based Taxation: Comparative Lessons for Indonesia from Singapore, The United States, and Nepal - Naury, Qowiya Hasna; Haptari, Vissia Dewi (Yayasan Ilomata, 2024)
This paper examines the implementation of tax policies that are in line with gender based taxation in Singapore, the United States and Nepal as well as policy recommendations that can be implemented in Indonesia through qualitative methods using literature studies and regulatory reviews. The discussion approached in several scopes; working women, corporate participation, caregiver, domestic work support, pink tax, women-owned businesses, widows, and taxation for families. In which this paper finds that Singapore, Nepal, and the United States have implemented a series of policies that create a more welcoming ecosystem for women to participate in economic activities, which Indonesia can use as an example in designing Gender Based Taxation in the future.